Assessment of Left Ventricular Reverse Remodeling by Echocardiography After 90 Days of Sacubitril/Valsartan Therapy in Patients of Heart Failure with Reduced Ejection Fraction - Akshay Pawar; Rajesh Rajani; Deepak Sadashiv Phalgune (Journal of Indian College of Cardiology)
Background: The present study aimed to assess the response of sacubitril/valsartan therapy on cardiac reverse remodeling (CRR) by standard and advanced echocardiographic parameters in patients of heart failure with reduced ejection fraction (HFrEF). Methods: One hundred and fifty patients ≥18 years of age with symptomatic heart failure with left ventricular ejection fraction (LVEF) <40.0% were included in this prospective observational study. All patients underwent baseline electrocardiography and standard echocardiographic examination. Patients were given sacubitril/valsartan maximal tolerated dose. Echocardiographic measurements were done after 90 days. The primary outcome measure was a change in LVEF, whereas the secondary outcome measures were changes in left ventricular dimensions and volumes, E/e’, pulmonary artery systolic pressure (PASP), and global longitudinal strain (GLS). Comparisons between two discrete variables and medians were performed using the Chi-square test/Fisher’s exact test and the Wilcoxon signed–rank test, respectively. Results: The median LVEF (32.5% vs. 30.0%) was significantly higher, whereas left ventricular end-diastolic volume (180 vs. 177.5 mL), left ventricular end-systolic volume (127.5 vs. 122.5 mL), left ventricular end-diastolic diameter (59 vs. 58 mm), left ventricular end-systolic diameter (51 vs. 50 mm), PASP (38 vs. 35), E/e’ (15 vs. 14), and GLS (−9.0 vs. −10.0) were significantly lower at 3-month follow-up as compared to baseline levels. Sacubitril/valsartan therapy leads to CRR as early as 90 days in patients with HFrEF. Conclusions: In HFrEF patients, sacubitril/valsartan significantly improved CRR.